Respon Phaeophleospora sp. Terhadap Fungisida Berbahan Aktif Metiram Secara in Vitro - Josua M Sitanggang; Edy Batara Mulya Siregar; Ridwanti Batubara (Peronema Forestry Science Journal, 2016)
Phaeophleospora sp is one of diseases which attack eucalyptus plant particulaily on eucalyptus nursery. This disease has been spread almost in the whole world. North Sumatera Control of the disease itself still use a fungicide and one of them is the fungicide active ingredient Metiram 70%. The purpose of this reseaech is to know the response of Phaeophleospora with fungicide Metiram substance 70% treatment with 0,4 ,0,8 ,1,2 and 1,6 mg/ml as concentrate. Response which measured was colony growth (wide, diameter, spora density, and change that happened to hifa). Research conducted at Forest Biothechnology Laboratory and Pest Plant Pathology Laboratory, Agriculture Faculty, University of North Sumatera. Used general linear non factorial with five times repetitions.        The 70% metiram treatment in 0,4, 0,8, 1,2 and 1,6 mg/ml  significant to the growth (wide, diameter, barriers relative and spore density) and also caused swelling on hyphae and change of form, tekstur and the color of colony Phaeophleospora sp. in vitro.Keywords : Phaeophleospora sp, Response In Vitro, Metiram 70%